Results of special laboratory testing program on Hackensack Valley varved clay / by Surendra K. Saxena, Jan Hedberg, Charles C. Ladd. - Saxena, Surendra Kumar, 1936-; Hedberg, Jan, author.; Ladd, Charles C. (Charles Cushing), author.; Massachusetts Institute of Technology. Department of Civil and Environmental Engineering.; Massachusetts. Department of Public Works.; United States. Federal Highway Administration. (Tufts University. Tisch Library., 2019)
1 online resource (185 pages) : illustrations.; "Prepared for Commonwealth of Massachusetts Department of Public Works in cooperation with U.S. Department of Transportation Federal Highway Administration."; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.